2011
DOI: 10.1039/c1cp21819k
|View full text |Cite
|
Sign up to set email alerts
|

Role of electromechanical and mechanoelectric effects in protein hydration under hydrostatic pressure

Abstract: Recent measurements of lysozyme hydration water density under non-denaturing pressure show that it is higher than that of bulk water in the same conditions. High protein hydration layer density has earlier been observed at ambient conditions and ascribed to electrostriction. We calculate the pressure-induced protein mean surface charge density increment Δσ. Within the hydration layer, the higher fields due to Δσ lead to an additional water compression via electrostriction. The increment Δσ is considered as due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…One is that pressure alters the waterwater hydrogen bonding energetics such that the unfolded state is favored at high pressure (11,12,50). Pressure-driven changes in the energetics of solvation of hydrophobic surfaces and of charged side chains have been argued to be significant (11,12,14). A more mechanical view is that pressure-induced unfolding is essentially a result of the relief of packing defects in the native conformations of proteins (3,5,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that pressure alters the waterwater hydrogen bonding energetics such that the unfolded state is favored at high pressure (11,12,50). Pressure-driven changes in the energetics of solvation of hydrophobic surfaces and of charged side chains have been argued to be significant (11,12,14). A more mechanical view is that pressure-induced unfolding is essentially a result of the relief of packing defects in the native conformations of proteins (3,5,51).…”
Section: Discussionmentioning
confidence: 99%
“…Fundamentally, pressure-induced unfolding of proteins results from the population of nonnative conformations having a lower total system volume than the native structure seen at ambient pressure. Various mechanisms for pressure-induced unfolding have been proposed including changes in water structure that weaken the hydrophobic effect at high pressure (11,12), increases in solvent density at the protein surface that contribute to a reduction in the total volume of the protein-water system (13,14), and the elimination of cavities in the protein interior through exposure to solvent (3). With the development of highpressure sample cells compatible with modern solution NMR probes (15), detailed measurements of proteins unfolding under pressure with atomic resolution have now become possible (5,(16)(17)(18).…”
mentioning
confidence: 99%
“…However, the exceptionally large piezoelectric coefficient of the cell demonstrates the unique role of the cell as a piezoelectric motor of biological importance, and it also indicates its potential applications for highly efficient biocompatible energy generators. Lysozyme, the antibacterial enzyme found in mammalian tears, saliva, and milk, also exhibits piezoelectric response 158,159. In 2017, Stapleton et al reported lysozyme can form two different crystalline structures, monoclinic and tetragonal, with piezoelectric properties, and the measured average piezoelectric coefficients were 0.94, and 3.16 pC N −1 , respectively (Figure 9d).…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 97%
“…Lysozyme, the antibacterial enzyme found in mammalian tears, saliva, and milk, also exhibits piezoelectric response. [158,159] In 2017, Stapleton et al reported lysozyme can form two different crystalline structures, monoclinic and tetragonal, with piezoelectric properties, and the measured average piezoelectric coefficients were 0.94, and 3.16 pC N −1 , respectively (Figure 9d). [160] The maximum piezoelectric coefficient of 6.5 pC N −1 was reached for the tetragonal aggregate film of lysozyme.…”
Section: Piezoelectricity Of Proteinsmentioning
confidence: 99%
“…23,24 The solvent in most of these studies is water as, in particular, all biological-relevant substances are dissolved therein. Water itself has several properties that are susceptible to pressure, such as the change of its density 25 and the dielectric constant, 26 pressure-induced electrostriction, 27 and the change of the pH value. 28 Moreover, at pressures close to 2000 bars, the collapse of the second hydration shell in water has been reported, which results in a steep and monotonic increase in the coordination number of water molecules.…”
Section: Introductionmentioning
confidence: 99%